A bi-tapered and air-gapped beam shaping assembly used for AB-BNCT. (January 2021) - Lee, Pei-Yi; Tang, Xiaobin; Geng, Changran; Liu, Yuan-Hao
Abstract: The 7 Li(p, n) 7 Be reaction, which leads to a soft neutron field, is often chosen as the neutron producing reaction used for accelerator-based boron neutron capture therapy (AB-BNCT). This study aims to design a compact beam shaping assembly (BSA) and auxiliary system for a 7 Li(p, n) 7 Be reaction-based neutron source and to evaluate the relationship between the BSA design and the consequent neutron beam quality for further optimization. In this study, five types of moderator shapes for the BSA model were designed. Both the in-air and in-phantom figures of merit were considered to evaluate the performance of the BSA designs. It was found that the BSA with a bi-tapered and air-gapped design could generate a high-intensity epithermal neutron beam, which could be used to treat deep-seated brain tumors within a reasonable time. Highlights: A compact beam shaping assembly and auxiliary system for the  7 Li(p, n) 7 Be reaction-based neutron source was designed. Five types of moderator shapes for the BSA model were evaluated. Both the in-air and in-phantom figures of merit were calculated to evaluate the neutron beam intensity and quality. The BSA with the bi-tapered and air-gapped design could produce a high intensity neutron beam with good penetrability.